Investigating of Trust and Perceived Organizational Support Effects on Organizational Commitment in Educational Organizations, using Structural Equation Modeling and Partial Least Squares Model - Rahmani, Saghar; Heydari, Marzieh (International Review of Management and Marketing, 2017)
The management and business policies of the educational institutions are focused based on human-dense settings, level of commitment of workers, values, and the manner of organizational commitment. To be more specific, trust in an organization as well as organizational commitment, and perceived organizational support (POS) are key constructs in management and organizational behaviour. Therefore, we have designed this study to peruse the relationship between dimensions of organizational commitment, trust and perceived organizational support on educational organizations, using Allen and Meyer’s method. Overall, we have used 385 questionnaires which have been completed by employees and members of separate subsidiaries of Islamic Azad University, Fars, Iran. Smart PLS (professional statistical software) has been used for data analysis. We have identified that the perceived organizational support has a significant and crucial efficacy on the dimensions of organizational commitment (p=0.481, 0.387, 0.184), while trust showed only a considerable established relationship with effective commitment (p=0.325), but no important positive correlation with continuance commitment (p= -0.331), as well as normative commitment (-0.081). Also, a remarkable positive correlation amongst trust and perceived organizational support (0.179) has been observed, which explains a mediating impress role of trust amongst organizational commitment and perceived organizational support. These finding shows the importance of trust and perceived organizational support in improving the educational organizations, in addition to creating organizational commitment. Keywords: Business Management Policy, perceived organizational support (POS), trust, organizational commitment, educational organization, Smart PLS JEL Classifications: L2, M1